Intellectual Autonomy of PhD Researchers who use the Grounded Theory Methodology - Andy Lowe (Grounded Theory Review: An International Journal)
The decision to choose the grounded theory methodology (GT) for one’s PhD research should never be done lightly, as outlined in Glaser (2015). The emergence of a researcher’s own intellectual autonomy is often of more importance than the research itself. Intellectual autonomy can be fostered perpetually and spasmodically.